Effects of depression, anxiety, stress, and partner relationship satisfaction on sexual dysfunction in women in the postpartum period. - Çankaya, Seyhan; Alan Dikmen, Hacer (Sexual & Relationship Therapy, 2023)
To determine the effects of depression, anxiety, stress, and partner relationship satisfaction on sexual dysfunction in women in postpartum first year, this cross-sectional study was conducted in a gynecological clinic in Turkey. Data belonging to 403 women in postpartum 12 months were analyzed. Data were collected using a multidimensional questionnaire, such as the Female Sexual Function Index, the Depression Anxiety and Stress Scale, and the Relationship Assessment Scale. The association between independent variables and sexual dysfunction was analyzed using the bivariate tests, such as the chi-square and independent sample t-tests and bivariate (binary) logistic regression analysis. Out of 403 women, 266 (66%) scored below the cutoff point (<26.5) for sexual dysfunction. Perineal tears/episiotomy/trauma during vaginal delivery, primiparity, increased depression, and anxiety, and relationship dissatisfaction in the postpartum period increase the risk of developing FSD by 26% (χ2 = 106.699, p < 0.001). In addition, women with higher stress levels were found to be more sensitive to sexual dysfunction symptoms. This study revealed that most women in the postpartum period had postpartum FSD. Midwives should evaluate women regarding their sexual functions during postpartum visits. Health education, counseling, referral services for early diagnosis, and treatment can contribute to maintain and improve women's sexual health in the postpartum period.